Examine the Effects of Various Chemicals and Different Environmental Conditions on the Breakdown of Dormancy of Dragon Fruit (Hylocereus undatus var. White Fleshed Pitaya) - Jassi Singh; Kunal Adhikary; Vartika Singh; Sudheer Pathak; Divya Pandey (Archives of Current Research International, 2024)
The dragon fruit, has attracted a lot of interest lately due to its eye-catching appearance and exceptional nutritional value. Despite its widespread use, little is known about the ideal circumstances for seed germination and the early stages of growth, such as the length of the seedling shoot, which are critical for the best crop production. By assessing the effects of different growing media on dragon fruit germination and early growth stages, this study seeks to close this gap. The experiment was laid out in the GPB (Genetics & Plant breeding) PG lab, Maxwell block, School of Agriculture (SOAG), ITM University, Gwalior, M.P. during 2024 in Completely Randomized Design with 9 treatments and 4 replications, i.e., T0 (Hydropriming in room temperature at 20-24˚C), T1 (Hydropriming 28˚C), T2 (Sand+ water mixture room temperature 20-24˚C), T3 (Sand+ water mixture in seed germinator 28˚C), T4 (Blotting sheet+ water in room temperature 20-24˚C), T5 (Blotting sheet+ water in seed germinator 28˚C), T6 (Citric acid treatment in room temperature 20-24, T7 (GA3 treatment 100 ppm Seed germinator at 28), T8 (TiO2 NPs 200 ppm Seed germinator at 28 Seeds were sown in petri plates on 26th February, 2024 in seed germinator and room temperature. The highest germination efficiency or percentage with 96.67%, followed by T8 (TiO2 NPs treatment in seed germinator at 28˚C) with 80% and T7 (GA3 treatment in seed germinator at 28˚C) with 78.33%, while T0 (Hydropriming in room temperature at 20-240C) has the lowest germination efficiency or percentage with 8.67%. The significantly highest seedling vigor index was recorded in T6 (Citric acid treatment room temperature at 20-24˚C) with 462.67 followed by T8 (TiO2 NPs treatment in seed germinator at 28˚C) with 353.67 and T7 (GA3 treatment in seed germinator at 28˚C) with 343.57 mg, while lowest seedling vigor index was recorded in T0 (Hydropriming in room temperature at 20-24˚C) with 32.67.